Effect of pyrolysis temperature on removal of organic pollutants present in anaerobically stabilized sewage sludge - Moško, Jaroslav; Pohořelý, Michael; Cajthaml, Tomáš; Jeremiáš, Michal; Robles-Aguilar, Ana A; Skoblia, Siarhei; Beňo, Zdeněk; Innemanová, Petra; Linhartová, Lucie; Michalíková, Klára; Meers, Erik (Chemosphere, 2021)
Sewage sludge was excluded from the list of component materials for the production of EU fertilizing products and it was banned as feedstock to produce pyrolysis & gasification materials in European Commission's technical proposals for selected new fertilizing materials under the Regulation 2019/1009 (STRUBIAS report). This exclusion of pyrolysis as a viable way to treat sewage sludge was mainly due to the lack of data on the fate of organic pollutants at pyrolysis conditions. In this work, we are addressing this knowledge gap. We studied slow pyrolysis as a potential process to efficiently treat organic pollutants present in stabilized sewage sludge. Sewage sludge was pyrolyzed in a quartz fixed bed reactor at temperatures of 400-800 °C for 2 h and the sludge and resulting sludge-chars were analyzed for the presence of four groups of organic pollutants, namely (i) polychlorinated biphenyls (PCBs), (ii) polycyclic aromatic hydrocarbons (PAHs), (iii) pharmaceuticals, and (iv) endocrine-disrupting and hormonal compounds. Pyrolysis at ≥ 400 °C effectively removed pharmaceuticals (group iii) to below detection limits, whereas pyrolysis at temperatures higher than 600 °C was required to remove more than 99.8% of the compounds from groups i, ii and iv. Based on these findings, we propose, that high temperature (>600 °C) slow pyrolysis can satisfactory remove organic pollutants from the resulting sludge-char, which could be safely applied as soil improver.
Keywords: Environmental Pollutants; látky znečišťující životní prostředí; pyrolýza; teplota; polycyklické aromatické uhlovodíky; odpadní vody; Temperature; Pyrolysis; Sewage; Polycyclic Aromatic Hydrocarbons